ChemInform Abstract: High‐Temperature Phase Transitions, Spectroscopic Properties, and Dimensionality Reduction in Rubidium Thorium Molybdate Family. Issue 21 (27th May 2014) - Xiao, Bin; Gesing, Thorsten M.; Kegler, Philip; Modolo, Giuseppe; Bosbach, Dirk; Schlenz, Hartmut; Suleimanov, Evgeny V.; Alekseev, Evgeny V.
Abstract Rb8Th(MoO4)6 (I), Rb2Th(MoO4)3 (II), Rb4Th(MoO4)4 (III), and Rb4Th5(MoO4)12 (IV) are prepared by solid state reaction of Th(NO3)4, RbNO3, and MoO3 in molar ratios of 1:2:2 for (I), 1:3:4 for (II), 1:2:4 for (III), and 1:1:1 for (IV), resp.